Drug–drug interactions in the management of non-tuberculous mycobacterial infections - Takeda, Kazuaki; Takazono, Takahiro; Mukae, Hiroshi (Frontiers in Microbiology, 2024)
Non-tuberculous mycobacterial pulmonary disease (NTM-PD) is a refractory chronic respiratory infectious disease and its prevalence is increasing globally. The standard treatment regimen for NTM-PD involves long-term multidrug therapy including macrolides. The incidence of adverse events is high given the advanced age of many NTM-PD patients. In addition, drug–drug interactions under coexisting conditions add additional complexity. Despite guidelines advocating multidrug therapy for NTM-PD, low adherence rates probably owing to the relatively frequent adverse events and drug interactions. An appropriate treatment regimen can improve the bacteriological response rates, reduce the development of macrolide resistance, and mitigate adverse events. Of particular concern are the interactions arising from new complications that develop with NTM-PD. Notably, chronic pulmonary aspergillosis occasionally co-infects NTM-PD, which can lead to poor prognosis. The primary therapeutic modality for chronic pulmonary aspergillosis is the azoles. However, the interaction with rifamycin is problematic, making it challenging to continue standard treatment for NTM-PD and requiring drug adjustments. The implications of rifamycin extend beyond chronic pulmonary aspergillosis, impacting various other diseases such as those requiring immunosuppressive agents and AIDS patients requiring antiretroviral therapy. Hence, a comprehensive consideration of drug interactions is imperative for the initiation of NTM-PD treatment. This mini-review focuses on drug–drug interactions in a multidrug regimen for NTM-PD and discusses the essential points to be considered in the treatment of NTM.